2016
DOI: 10.3847/0004-637x/832/2/170
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Supersonic Evershed Downflows

Abstract: We study supersonic Evershed downflows in a sunspot penumbra by means of high spatial resolution spectropolarimetric data acquired in the Fe I 617.3 nm line with the CRISP instrument at the Swedish 1-m Solar Telescope. Physical observables, such as Dopplergrams calculated from line bisectors and Stokes V zero-crossing wavelengths, and Stokes V maps in the far red wing, are used to find regions where supersonic Evershed downflows may exist. We retrieve the LOS velocity and the magnetic field vector in these reg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…While umbral magnetic fields are barely inclined relative to the local surface normal and primarily expand into the upper solar atmosphere, the magnetic field lines in the penumbra show a mixture of different inclination angles (e.g., Solanki 2003;Bellot Rubio et al 2004;Beck 2008). Some of the magnetic field lines return back to the photosphere within the penumbra (del Toro Iniesta et al 2001;Franz & Schlichenmaier 2013; Ruiz Cobo & Asensio Ramos 2013; Esteban Pozuelo et al 2016), while some others continue upwards and outwards into the so-called superpenumbra that is seen in chromospheric diagnostics to extend beyond the sunspot boundary visible in the photosphere (Joshi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…While umbral magnetic fields are barely inclined relative to the local surface normal and primarily expand into the upper solar atmosphere, the magnetic field lines in the penumbra show a mixture of different inclination angles (e.g., Solanki 2003;Bellot Rubio et al 2004;Beck 2008). Some of the magnetic field lines return back to the photosphere within the penumbra (del Toro Iniesta et al 2001;Franz & Schlichenmaier 2013; Ruiz Cobo & Asensio Ramos 2013; Esteban Pozuelo et al 2016), while some others continue upwards and outwards into the so-called superpenumbra that is seen in chromospheric diagnostics to extend beyond the sunspot boundary visible in the photosphere (Joshi et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, many comparative and statistical studies between both spectral bands have been carried out at this angular resolution (Schlichenmaier & Collados 2002;Müller et al 2002;Borrero et al 2007;Borrero & Solanki 2010). At highspatial resolution (i.e., < 0.5") similar studies have been conducted in visible (Ichimoto et al 2007(Ichimoto et al , 2008Franz & Schlichenmaier 2013;Pozuelo et al 2016), and NIR spectral lines (Franz et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…de la Cruz Rodríguez, 2015, 2016, and the references therein). Supersonic vertical velocities at the outer end of penumbral filaments have been reported (Figure 4) and can be associated with penumbral field lines dipping down below the solar surface (Tiwari et al, 2013;Esteban Pozuelo, Bellot Rubio, and de la Cruz Rodríguez, 2016), but similar flows have also been detected in the inner penumbra without relation to the Evershed flow (Louis et al, 2011). In both regions, very large field strengths (on the order of 7 kG and 5 kG, respectively, compared to typical peak umbral values of 2 -3 kG) have been associated with the high-speed flows (Siu-Tapia et al, 2017;Okamoto and Sakurai, 2018), but because the observed Stokes profiles show anomalous shapes, these determinations are uncertain.…”
Section: Active Region Evolution and Sunspot Fine Structurementioning
confidence: 79%